2018
DOI: 10.13189/ujer.2018.060523
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of ICT Integration Approach Scale to Kosovo Culture: A Study of Validity and Reliability Analysis

Abstract: The aim of this study is to adapt ICT integration approach scale to Kosovo culture, which measures ICT integration approaches of university faculty to teaching and learning process. The scale developed in Turkish has been translated into Albanian to provide linguistic equivalence. The survey was given to a total of 303 instructors [161 (53.1%) females and 142 (46.9%) males] for the Confirmatory Factor Analysis of the scale. In the first analysis of the scale, fit indices were obtained in support of 3 factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…In some scale studies conducted in different cultures (Gjersing et al, 2010;Kornor et al, 2007;Meyer, Eley, 2006;Sandhu et al, 1996;Schellhase, 2009), it was observed that different results were determined due to cultural differences. However, as in the present study, some studies conducted in different cultures (Lopez-Fernandez, 2017;Kervan, Tezci, 2018;Kervan et al, 2021;Uysal-Bozkir et al, 2013) also produced results showing that similar factor structures were supported.…”
Section: Discussionsupporting
confidence: 84%
“…In some scale studies conducted in different cultures (Gjersing et al, 2010;Kornor et al, 2007;Meyer, Eley, 2006;Sandhu et al, 1996;Schellhase, 2009), it was observed that different results were determined due to cultural differences. However, as in the present study, some studies conducted in different cultures (Lopez-Fernandez, 2017;Kervan, Tezci, 2018;Kervan et al, 2021;Uysal-Bozkir et al, 2013) also produced results showing that similar factor structures were supported.…”
Section: Discussionsupporting
confidence: 84%